Effects of Jianpi Qingchang decoction on the quality of life of patients with ulcerative colitis: A randomized controlled trial. Issue 16 (April 2017) - Dai, Yan-Cheng; Zheng, Lie; Zhang, Ya-Li; Chen, Xuan; Chen, De-Liang; Tang, Zhi-Peng
Abstract : Abstract: This study aims to determine the effects of the Jianpi Qingchang decoction (JQD) on the quality of life (QOL) of patients with spleen deficiency and dampness-heat syndrome ulcerative colitis (UC). A total of 120 active UC patients with spleen deficiency and dampness-heat syndrome were enrolled into this study. These patients were randomly divided into 2 groups: test group and control group (n = 60, each group). Patients in the test group were treated with JQD, while patients in control group were treated with 5-amino salicylic acid. After treatment for 8 weeks, differences in inflammatory bowel disease questionnaire (IBDQ) scores, short form-36 health survey questionnaire (SF-36) scores, and Sutherland Disease Activity Index (DAI) values were compared between these 2 groups to assess the QOL of patients. Sutherland DAI scores decreased in both groups after the treatment, but the difference was not statistically significant ( P < .05). However, the difference in bowel symptoms, systemic symptoms, total scores of the 4 IBDQ dimensions (physical function, bodily pain, vitality, and mental health), and total scores of the SF-36 questionnaires between these 2 groups were statistically significant ( P < .05). JQD can be used as supplementary and alternative therapy to relieve clinical symptoms in patients with mild to moderate active UC, and consequently improve their QOL.